Krytyka modernizmu i integryzmu w personalizmie chrześcijańskim - Witko, Krzysztof (Studia Pastoralne, 2026)
In the new and uncomfortable situation Christians sometimes adopt two equally ineffective attitudes: liberal modernism and religious integralism. Following Emmanuel Mounier (1905–1950) I start my analysis with a reflection on “the space” of modernism – a situation of a Christian subjected to “the world outside”, a victim of alleged modernity and scientistic rationalism. Next I analyse religious integralism, which is blind acceptance of doctrines and articles of faith without any proof. This attitude approves, to some extent, the status quo and treats it as something irreversible. In my conclusion I present my conviction that the area of personalistic thinking is Christianity rooted in the Paschal mystery of Christ and at the same time involved one, participating in human affairs, open to the question of meaning of human existence.